The Relationship Between Sleep Patterns, Sleep Quality, and Recurrent Infections with the Incidence of Stunting in Toddlers - Sri Raudhati; Siti Saleha; Zaitun Hilwa (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2026)
Stunting is a condition of growth failure in toddlers caused by chronic malnutrition, recurrent infections, and environmental factors during the critical first 1,000 days of life. Sleep patterns and sleep quality in toddlers are among the risk factors for stunting. This study aimed to analyze the relationship between sleep patterns (duration, efficiency, and sleep disturbances) and the incidence of stunting in toddlers aged 24–59 months, as well as to identify factors influencing sleep quality among stunted toddlers in the working area of Pandrah Public Health Center, Bireuen District. This research uses a quantitative design with a cross-sectional approach. Data were collected using the Brief Infant Sleep Questionnaire (BISQ) and anthropometric measurements of toddlers to determine stunting status. The sample consisted of toddlers aged 24–59 months selected through purposive sampling from the health center’s working area. Data analysis was performed using the Chi-Square test to examine the association between sleep pattern and sleep quality variables with stunting incidence. The results showed that most of the studied toddlers were aged 3.00–4.11 years with a relatively balanced gender distribution. The majority had regular sleep patterns, but many demonstrated poor sleep quality. Chi-Square test results indicated a significant association between sleep patterns and sleep quality with stunting incidence in toddlers (p < 0.005). The study concludes that there is a significant relationship between sleep patterns and sleep quality with stunting among toddlers. Therefore, behavior-based interventions, such as educating parents about consistent sleep routines and creating a conducive sleep environment, should be considered as part of stunting prevention programs.